Peningkatan Efisiensi Kompor LPG dengan Menggunakan Elemen Bara Api - Sudarno sudarno sudarno; Fadelan Fadelan (Semesta Teknika, 2016)
The defective combustion process is one of the causes of low efficiency in LPG stoves. Increasing the efficiency in LPG stoves by optimizing the combustion has high possibility to do. Practical effort that can be done is adding the element embers. This tool is a woven wire nikelin that are arranged in layers and if it is heated, it will be incandescent, forming high temperature embers. Generated embers will be able to burn fuel vapor perfectly around the wire, so it will broaden the mature fire area. The test is done by using LPG stoves which is provided by finned heat radiation reflector. The efficiency test is done by conducting the boiling water test. The number of element embers layers are varied, from one to four layers. The performance of element embers use is compared with LPG stoves without element embers use. In this study, temperature distribution for each treatment is tested. It is obtained that the use of element embers without reflector can improve the efficiency until 8.23%. The highest efficiency occurred in one of layer element embers use, as much as 61.7%. But, the increase of element embers in finned heat radiation reflector decreased the efficiency. It was because the mounting pattern of element embers bothered the function of the reflector, so the heat reflection from the reflector was stunted and stuck between the reflector and the mounting pattern. Therefore, the heat energy of the reflection from the reflector cannot be moved to combustion area. The result of temperature distribution test also showed that the element embers use could broaden the mature fire area.